Review of the evidence for the potential impact and feasibility of substituting saturated fat in the New Zealand diet - Rachel H. Foster; Nick Wilson (Elsevier, 2013)
Abstract Objective: To estimate the potential impact on cardiovascular health of modifying dietary intake of saturated fat across the New Zealand population, and whether this would be appropriate and feasible. Methods: First, a literature review of meta‐analyses was conducted to estimate the magnitude of reduction in risk for cardiovascular events in response to a reduction in dietary saturated fat intake (with or without substitution with other macronutrients). Second, data from the New Zealand Adult Nutrition Survey 2008/09 were used to determine whether a change to the population's dietary fat intake would be warranted and feasible. Results: Five relevant meta‐analyses were identified. No significant association between saturated fat intake alone and cardiovascular disease was found. However, the incidence of cardiovascular disease events was less when dietary saturated fats were replaced with polyunsaturated fats, reducing the risk of cardiovascular events by about 10%. Compared with nutritional guidelines, New Zealanders' current saturated fat intake is excessive while polyunsaturated fat intake is inadequate; both would be corrected by a substitution of 5% of daily energy intake. Conclusions: Replacing 5% of daily energy consumed as saturated fat with polyunsaturated fats would be expected to reduce cardiovascular events by about 10%. Implications: In order to achieve the population‐wide dietary fat modifications needed to improve cardiovascular health for New Zealanders, a public health strategy (e.g. fiscal, regulatory and/or educational interventions) must be implemented. Further work is needed to establish the cost‐effectiveness of the various strategies.